FRESHWATER NEMATOFAUNA (NEMATODA) IN A SEMI-ARID REGION - Barros, Fábio Lucas de Oliveira; Silva, Maria Cristina da; Vieira, Alecxandro Alves; Castro, Francisco José Victor de (Revista Nordestina de Zoologia, 2020)
Nematodes are a group of invertebrates found in all aquatic ecosystems, exhibiting great abundance and diversity. The present study was undertaken in the towns of Araruna, Cacimba de Dentro and Tacima, located in the microregion of eastern Curimataú, in the state of Paraiba. Three sampling points were determined with three replicates each, using a PVC tube with an internal area of 15.68 cm2 for the removal of the material, and the samples were taken to the laboratory for analysis. The Nematofauna community exhibited 16 genera. The processes of drought and consequently the evaporation, precipitation and salinity allied to the same, as well as the urbanization of certain reservoirs, are factors that contribute to the establishment of nematofauna assemblies.